Room-temperature ferromagnetism in Ni-doped TiO2 diluted magnetic semiconductor thin films - Parveen, Bushra; Mahmood-ul-Hassan; Khalid, Zeeshan; Riaz, Saira; Naseem, Shahzad (Journal of applied research and technology, 2017)
We report undoped and Ni-doped TiO2 (xNi=0.00, 0.50, 1.00, 1.50, 2.00 and 2.50wt.%) thin films fabricated on glass substrates by using a combination of solid-state reaction and dip coating techniques. The structural properties are observed by X-ray diffraction (XRD), which have depicted that annealing at 650°C results in rutile Ni-doped TiO2 as a major phase along with a minor anatase phase. The surface morphology of the deposited thin films, as measured by scanning electron microscopy (SEM), indicates granular spherical shaped nanostructures. Room-temperature ferromagnetism (RTFM) has been illustrated by all the grown thin films, as elucidated by vibrating sample magnetometer (VSM). Although Ni content has no pronounced effect on the crystallinity that indicates a substitutional replacement of Ni in TiO2 lattice, however, Ni content is observed to influence the ferromagnetic behavior. Therefore, the present study signifies the potential spintronic applications of Ni-doped TiO2 diluted magnetic semiconductors, fabricated by a low-cost method, as it exhibits RTFM with nanograins at the surface.